Detection of orchid viruses by analyzing Brownian diffusion of nanobeads and virus–immunobead association. Issue 13 (9th June 2015) - Fan, Yu-Jui; Chang, Ya-Chun; Teng, Chao-Ti; Liao, Ting-Ya; Hu, Wen-Chi; Sheen, Horn-Jiunn
Abstract : This paper describes a new sensing technique for detecting orchid viruses by measuring the Brownian diffusion of immunobeads in liquid samples. Abstract : This paper describes a new sensing technique for detecting orchid viruses by measuring the Brownian diffusion of immunobeads in liquid samples. Both the capsid proteins and virus particles of Odontoglossum ringspot virus (ORSV) are detectable targets by using this technique. When the targets bind to immunobeads, the Brownian diffusion of the beads decreases. Thereafter, the kinetic model of the antibody–antigen interaction in a free liquid space can be established. This model is used to calculate the association constant rate, dissociation constant rate, and dissociation constant of ORSV capsid proteins and antibody-coated nanobeads. This paper presents the results of using 300 nm immunobeads to detect ORSV capsid proteins and particles in a phosphate-buffered saline solution, as well as the results of using 500 nm beads to detect ORSV particles in a plant sap solution. In addition, transmission electron microscopy images of the antibody-coated nanobeads reacting to low and high concentrations of the ORSV are shown.